Is Lateral Ligament Complex Repair Necessary in All Unstable Elbow Injuries with Coronoid Fractures? A Comparative Study: A Case Series - Nishaanth Ragavan; Rex Chandrabose (Journal of Orthopedics and Joint Surgery)
Background: Unstable elbow injuries result in persistent discomfort, recurring instability, stiffness, and arthritis. The coronoid is prone to fracture as a result of axial stress and it serves as an anterior buttress that prevents the posterior ulna translation. In order to restore the bone and ligamentous components and allow for early mobilization, the protocol was formulated. Unfortunately, there was no clear idea regarding the surgical approach and essential structures to be restored for adequate elbow stability. Hence, our study was conducted to find out the appropriate structures and approaches to provide elbow stability and better functional outcomes. Materials and methods: A total of 28 patients (20 men and eight women) who had closed elbow dislocation with associated coronoid fracture and lateral ligament complex injury were studied prospectively. The patients were divided into two groups, group I included patients who underwent only coronoid fixation, and group II included patients who underwent both coronoid fixation with lateral ligament complex repair. In group II, the lateral collateral ligament complex was repaired only when the lateral approach was used in case of radial head fixation, radial head replacement, or excision. Wrightington's classification describes the cross-sectional findings in complex elbow fracture-dislocation injury was used. Magnetic resonance imaging (MRI) with computed tomography (CT) evaluation was done in all cases to assess the osseous and ligamentous status to select the appropriate surgical approach and method of fixation. Functional outcome was assessed using the Mayo Elbow Performance Score (MEPS) at 6 weeks, 3rd, 6th months, 1, and 2 years. Results: All patients in our study were treated surgically according to Wrightington's classification. Treatment is done as follows—coronoid process fixation with suture anchors, mini plate, and screws by medial Hotchkiss approach or modified anterior approach. Radial head fractures by fixation, excision, or radial head replacement. Associated olecranon fractures were fixed with locking compression plate (LCP) or tension band wiring. Functional outcome analyzed using MEPS shows excellent in 18 patients, good in nine patients, and fair in one patient. Conclusion: Not all patients with unstable elbow injuries need to follow the standard protocol for fixation. Restoring the elbow integrity with the appropriate method of fixation and approach is sufficient to provide a functional and stable elbow.